Renovation Regarding The Origin Of Subject Indication Concerning Al-Ragib Al-Asfahani - Elshahed, Wafaa Mohamed (Journal of Arabic Language Sciences and Literature, 2023)
This study is originally a section of a Master’s thesis in Arabic linguistics. It focuses on the renovation points regarding the origin of subject indication concerning Al-Ragib Al-Asfahani that can be clear only through a comparison between Al-Ragib Al-Asfahani and Ibn Faris in their stances about it.Since research in dictionaries needs an objective approach that requires follow up, investigation, analysis, interpretation, classification, measurement, correlation and results, the researcher has chosen the topic to be dictionary-wise and the study approach to be descriptive, interpretative and comparative. The study also focused on the renewal in the fundamentals theory by Al-Ragib, considering that he was a century or more late than Ibn Faris. This renewal is presented in some connotations, synonyms, fundamental phrases and how to distinguish it from the branch. Also, to cast light on some of its evidences, its clearness or ambiguity and to frame it in sensual meanings, since, according to his point of view, they surpass moral meanings. Also, not to consider abnormality on the branches and get help from metaphor and attribute it to the indication origin, and there had been no terms for the origin or its description.
Keywords: The origin of subject indication; Renovation; Al-Ragib and Al-Asfahani